(untitled) (Asian Journal of Social Science Studies, 2025)
This study investigates the governance of industrial parks in Africa, with a particular focus on the contributions from BRICS nations and other emerging economies. Employing a comparative method through a thorough review of secondary sources, this research aims to analyze how diverse governance models influence the capacity of industrial parks to attract investments, ensure operational efficiency, and promote sustainable economic growth. The findings reveal that BRICS countries, notably China and India, have played a pivotal role in shaping governance structures, exemplified by successful case studies in 11 selected African countries. This research enriches existing theories on institutional governance and developmental states while identifying critical challenges, including bureaucratic inefficiencies and corruption. Furthermore, it offers actionable recommendations for policymakers aimed at enhancing industrial park governance in Africa. By establishing a roadmap for future research, this study lays the foundation for examining the long-term effects of BRICS engagement and the adaptation of governance models across various African regions. Ultimately, the results underscore the significance of effective governance in driving industrial growth and supporting the broader economic development aspirations of the continent.